Functional analysis of StWRKY75 gene in response to heat stress in potato (Solanum tuberosum L.) - Zhu, Xi; Duan, Xiaoqin; Majeed, Yasir; Luo, Junfu; Guan, Nengkang; Zheng, Haifei; Zou, Huafen; Jin, Hui; Chen, Zhuo; Zhang, Yu (Frontiers in Plant Science, 2025)
Heat stress severely restricts potato tuber growth and development, yet the roles of WRKY transcription factors (TFs) in mediating heat responses remain poorly understood. Using quantitative reverse transcription PCR (qRT-PCR), we identified StWRKY75 in potato cultivars ‘Atlantic’ and ‘Desiree’ as a heat-inducible gene, showing significant upregulation under 30°C and 35°C treatments. Phylogenetic analysis classified StWRKY75 into the WRKY Group II family, with close evolutionary homology to tomato SlWRKY75, and subcellular localization confirmed its nuclear targeting. To characterize its function, we generated transgenic lines overexpressing StWRKY75 (OE) or knockdown by RNA interference (RNAi). Under heat stress conditions, OE plants demonstrated superior thermotolerance compared to non-transgenic (NT) controls, manifested by improved growth parameters (plant height, tuber weight per plant, fresh weight, dry weight, root fresh weight, and root dry weight), enhanced activities of antioxidant enzymes (ascorbate peroxidase [APX], catalase [CAT], peroxidase [POD], and superoxide dismutase [SOD]), increased proline accumulation, elevated photosynthetic efficiency, and reduced malondialdehyde (MDA) content. Conversely, RNAi lines exhibited compromised thermotolerance with reversed growth parameters and biochemical characteristics. qRT-PCR analysis revealed that StWRKY75 positively regulated key heat-stress responsive genes, including those encoding antioxidant enzymes (StAPX, StCAT, StSOD, StPOD), proline biosynthesis Pyrroline-5-carboxylate synthase (StP5CS), and heat shock proteins (StHSP20, StHSP70, StHSP90). These findings demonstrate that StWRKY75 acts as a positive regulator of potato thermotolerance by enhancing growth, antioxidant capacity, proline metabolism, photosynthesis, and heat-responsive gene expression, providing a valuable target for improving crop heat resilience in breeding programs.